Seasonal Variation in Canopy Size, Light Penetration and Photosynthesis of Three Cassava Genotypes with Different Canopy Architectures - Supattra Mahakosee; Sanun Jogloy; Nimitr Vorasoot; Piyada Theerakulpisut; C. Corley Holbrook; Craig K. Kvien; Poramate Banterng (Agronomy, 2020)
The objective of this study was to investigate the effect of canopy size (CS) on light penetration and leaf photosynthesis of three cassava genotypes (Kasetsart 50 (KU50), Rayong 11 and CMR38-125-77) under two planting dates in two years. Data were recorded for CS, leaf area index (LAI), leaf photosynthesis, biomass (BM), storage root yield (SRY), starch content (SC) and harvest index (HI). The variation of CS depended on temperature, solar radiation (SR), relative humidity (RH) and day length (DL). In early growth stages, the crops planted in May had higher CS than the crops planted in November, because they were subjected to higher temperature, more SR, higher RH and longer DL. In contrast, the storage root accumulation of the crops planted in November was under better climatic factors than the crops planted in May. Therefore, the crops planted in November had higher BM and SRY than the crops planted in May for KU50 and CMR38-125-77. However, Rayong 11 in the May planting date maintained higher CS during storage root accumulation than the other genotypes, and BM and SRY of Rayong 11 were not different for the two planting dates in both years. KU50 and CMR38-125-77 had higher BM and SRY in the November planting, whereas in the May planting, the SRY and BM of the three genotypes were not significantly different. Genotypes that maintained high CS at the storage root accumulation stage could be indirectly selected for high BM and SRY in cassava breeding programs.